The Effect of Monetary Policy on Bank Wholesale Funding - Choi, Dong Beom; Choi, Hyun-Soo (Management Science, 2021)
We study how monetary policy affects the funding composition of the banking sector. When monetary tightening reduces the supply of retail deposits, banks attempt to substitute wholesale funding for deposit outflows to smooth their lending. Because of financial frictions, banks have varying degrees of access to wholesale funding. Therefore, large banks, or those with greater reliance on wholesale funding, increase their wholesale funding more. Consequently, monetary tightening increases both the reliance on and the concentration of wholesale funding within the banking sector. Our findings also suggest that liquidity requirements could bolster monetary policy transmission through the bank lending channel. This paper was accepted by Tyler Shumway, finance.